2000
DOI: 10.1073/pnas.97.16.9082
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the gene encoding the proapoptotic Nip3 protein is induced by hypoxia

Abstract: The ability to sense and respond to changes in oxygen availability is critical for many developmental, physiological, and pathological processes, including angiogenesis, control of blood pressure, and cerebral and myocardial ischemia. Hypoxia-inducible factor-1␣ (HIF-1␣) is a basic-helix-loop-helix (bHLH)-containing member of the PER-ARNT-SIM (PAS) family of transcription factors that plays a central role in the response to hypoxia. HIF-1␣, and its relatives HIF-2␣͞endothelial PAS domain protein (EPAS) and HIF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

27
538
2

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 696 publications
(573 citation statements)
references
References 27 publications
27
538
2
Order By: Relevance
“…In agreement with the previous reports (Bruick, 2000;Guo et al, 2001), hypoxia induced the expression of Bnip3 in all of the cell lines used in this study. Bnip3 is a mitochondrial protein and induces apoptosis independently of Apaf-1, cytochrome c release and caspase activation .…”
Section: Discussionsupporting
confidence: 94%
“…In agreement with the previous reports (Bruick, 2000;Guo et al, 2001), hypoxia induced the expression of Bnip3 in all of the cell lines used in this study. Bnip3 is a mitochondrial protein and induces apoptosis independently of Apaf-1, cytochrome c release and caspase activation .…”
Section: Discussionsupporting
confidence: 94%
“…Of the remaining five lines, two (TALL1 and Raji) expressed only negligible levels of BNIP3, and three (SupT1, PEER and KHM1B) expressed none at all. The earlier findings that under hypoxic conditions expression of BNIP3 can be induced by the transcription factor HIF-1a (Bruick, 2000;Guo et al, 2001;Sowter et al, 2001) prompted us to evaluate the extent to which expression of BNIP3 in haematopoietic tumour cell lines could be induced by hypoxia. Using real-time PCR with cDNA prepared from Jurkat and SupT1 cells incubated under hypoxic conditions, we found that hypoxia leads to increased expression of BNIP3 in Jurkat cells but not in SupT1 cells ( Figure 1B).…”
Section: Resultsmentioning
confidence: 99%
“…Hypoxia induces expression of a group of genes, among which is the transcriptional regulator HIF-1. BNIP3 is a principle target of HIF-1, and the region containing BNIP3's transcription start site also contains HIF-1-binding sequences (Bruick, 2000;Sowter et al, 2001). It is noteworthy that because HIF-1 is involved in both survival and apoptosis of tumour cells, abrogation of the apoptotic pathway caused by silencing BNIP3 may enhance HIF-1-induced survival signals within tumours.…”
Section: Discussionmentioning
confidence: 99%
“…41 Treated cells were collected with trypsinization, washed twice with PBS, and stained with 150 nM TMRE in PBS in the dark at 371C for 30 min. Samples were washed and resuspended with PBS containing 15 nM TMRE and then analyzed with the FACScan using CellQuest software.…”
Section: Flow Cytometric Analysis Of Mitochondrial Membrane Potentialmentioning
confidence: 99%